Pendidikan Lingkungan pada Anak Melalui Ecoprint: Penelitian - Fitria Rhamadona; Nadiah Azlila; Siti Khodizah Harahap; Dhea Ayuanda; Teuku Alfi Syahrin; Hidayat (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The abstract of this article is prepared in a standard format that includes a brief background, objectives, methods, quantitative results, and contributions/implications of the research. This study aimed to introduce ecoprinting techniques to children aged 7 to 12 in Sei Simujur Village. Ecoprinting is a creative method that combines art with sustainability, using natural materials to print colors and shapes on various media. Within the context of environmental awareness, this activity was designed to educate the younger generation about environmentally friendly ways of creating art. Using a descriptive qualitative approach, the researchers directly observed the children's interactions with the ecoprinting technique. The post-test results showed an average score of 88.6, with 67% of respondents scoring above 80. These findings indicate that the ecoprinting activity successfully increased children's understanding of environmental conservation and developed their creativity. This study recommends similar activities to expand environmental education to more children.